The reciprocal relationships between changes in adolescent perceived prevalence of smoking in movies and progression of smoking status. Issue 5 (9th August 2011) - Choi, Kelvin; Forster, Jean; Erickson, Darin; Lazovich, DeAnn; Southwell, Brian G
Abstract : Background: Smoking in movies is associated with adolescent smoking worldwide. To date, studies of the association mostly are restricted to the exposure to smoking images viewed by 9–15-year-olds. The association among older adolescents is rarely examined. In addition, the reciprocal effect of smoking behaviour on subsequent reported exposure to smoking in movies has not been reported. Methods: Data were from the Minnesota Adolescent Community Cohort Study collected every 6 months from 2000 to 2007 when participants were between the ages of 12 and 18 (n=4745). We estimated the prospective effect of the perceived prevalence of smoking in movies (four levels, from never to most of the time) on smoking stage (SS) measured 6 months later (six stages, from never-smoker to established smoker) and the reciprocal prospective association between the two factors. Estimates were adjusted for demographic factors. Results: The perceived prevalence of smoking in movies measured between ages 13½ and 15½ consistently predicted subsequent SS. The association was inconsistent after the age of 15½. SS did not consistently predict subsequent perception of the prevalence of smoking in movies. Conclusions: Perceived exposure to movie smoking primarily influenced teenagers' smoking behaviour at younger ages. If future studies confirm this finding, developing and evaluating interventions to improve young teenagers' resistance to these images may complement policies to reduce smoking in movies to reduce prevalence of adolescent smoking.